Vladimir I. Arnold - Collected Works Hydrodynamics, Bifurcation Theory, and Algebraic Geometry 1965-1972 - Arnold, Vladimir I. (Vladimir I. Arnold - Collected Works, 2014)
Vladimir Arnold was one of the great mathematical scientists of our time. He is famous for both the breadth and the depth of his work. At the same time he is one of the most prolific and outstanding mathematical authors. This second volume of his Collected Works focuses on hydrodynamics, bifurcation theory, and algebraic geometry.